2017
DOI: 10.1007/s00246-017-1582-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fluid Responsiveness in Children Undergoing Cardiac Surgery After Cardiopulmonary Bypass

Abstract: Dynamic parameters of fluid responsiveness (FR), namely aortic blood flow velocity variation (delta V ), left ventricular velocity-time integral variation (delta VTI), stroke volume variation, and pulse pressure variation (PPV) have demonstrated good diagnostic performance for the prediction of response to fluid loading in mechanically ventilated critically ill adult patients. We aimed to evaluate these parameters in children undergoing cardiac surgery. A retrospective observational study of mechanically venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…In children after cardiopulmonary bypass, the compliance of chest wall, lung, and arterial vascular system may be much reduced due to systemic inflammatory response and ischemia‐reperfusion injury . As a result, it is not surprising that more recent studies, including ours, have found the predictivity of fluid responsiveness of PPV in this particular group of children …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In children after cardiopulmonary bypass, the compliance of chest wall, lung, and arterial vascular system may be much reduced due to systemic inflammatory response and ischemia‐reperfusion injury . As a result, it is not surprising that more recent studies, including ours, have found the predictivity of fluid responsiveness of PPV in this particular group of children …”
Section: Discussionmentioning
confidence: 69%
“…25 As a result, it is not surprising that more recent studies, including ours, have found the predictivity of fluid responsiveness of PPV in this particular group of children. 9,11,26 5 | CONCLUSION PPV is predictive of fluid responsiveness in VSD and TOF patients following cardiac surgery. The predictivity in VSD patients is with higher magnitude of PPV, ROC curve area, and cutoff value as compared to TOF patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Validation of dynamic indictors of filling in children is ongoing, but is complicated by the differences in size, physiology and ventilation practice across age groups. In small cohorts of similar patients, these indicators perform well, but across large heterogeneous populations the aggregate results are less reliable, though still better than the use of the CVP (which approximates a coin toss in its predictive ability in several studies). Clinicians wanting to utilize these metrics in 2019 need to understand them in detail, and the most recent evidence relevant to their pediatric anesthesia practice.…”
Section: Fluid Responsiveness and Preload Measurementmentioning
confidence: 98%
“…Several indices have been studied in children with the aim to determine those which are suitable in pediatric patients. Parameters like pulse pressure variation (PPV) to assess fluid responsiveness remain until now controversial in children [5][6][7][8]. One important aspect is to have a non invasive tool or monitor to determine these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A possible non invasive tool is trans-thoracic echocardiography. An indice like trans-thoracic aortic blood flow peak velocity variation (ΔV peak) has been validated as an accurate parameter of fluid responsiveness in ventilated children in several trials [5][6][7][8]. Since this indice has been validated to predict fluid responsiveness in several pediatric studies, it will be integrated in this prospective randomized controlled trial (RCT) to determine the impact of intraoperative goal directed fluid and hemodynamic therapy (GDFHT) with this parameter on postoperative outcome in high risk pediatric patients in major surgery.…”
Section: Introductionmentioning
confidence: 99%